Antioxidant, antibacterial, and antifungal activity of Hymenochaete rubiginosa - Inci, Sule; Sevindik, Mustafa; Kirbag, Sevda; Akgul, Hasan (Natl Inst Science Communication & Information Resources-Niscair, 2022)
The use of fungi in alternative medicine and their use as pharmacological agents is gradually increasing today. Hymenochaete rubiginosa (Dicks.) Lev, locally known as Crust, is a species that belongs to the Polyporales family. In this study, it was aimed to determine the antimicrobial and antioxidant activity of H. rubiginosa extracts obtained from ethanol solvent. Its antimicrobial activity has been determined using the microdilution (MIC) method. In this study, bacteria such as Staphylococcus aureus ATCC 29213, Staphylococcus aureus MRSA ATCC 43300, Enterococcus faecalis ATCC 29212. Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853 and Acinetobacter baumannii ATCC 19606 and Candida albicans ATCC 10231, Candida krusei ATCC 34135 and Candida glabrata ATCC 9003 have been used as fungi. Total antioxidant level (TAS), total oxidant level (TOS) and oxidative stress index (OSI) values were calculated for antioxidant activity. According to the results obtained, it has been determined that the ethanol extract of H. rubiginosa showed antimicrobial effect against test microorganisms at concentrations of 25-200 mu g/mL. The TAS value of H. rubiginosa has been determined as 6.313 +/- 0.050 mmol/L, TOS value as 14.358 +/- 0.202 mu mol and OSI value as 0.227 +/- 0.002. As a result, it has been determined that H. rubiginosa can be used as an antioxidant and antimicrobial agent in pharmacological designs.
Keywords: Antimicrobial; Antioxidant; Hymenochaete rubiginosa; Medicinal mushroom; Oxidant